Altered replication and inverted repeats induce mismatch repair-independent recombination between highly diverged DNAs in yeast. - Tran, H (1997)
Replication, DNA organization, and mismatch repair (MMR) can influence recombination. We examined the effects of altered replication due to a mutation in the polymerase delta gene, long inverted repeats (LIRs) in motifs similar to those in higher eukaryotes, and MMR on intrachromosomal recombination between highly diverged (28%) truncated genes in Saccharomyces cerevisiae. A combination of altered replication and an LIR increased recombination up to 700-fold, while each alone led to a 3- to 20-fold increase. Homeologous recombination was not altered by pms1, msh2, and msh3 mismatch repair mutations. Similar to our previous observations for replication slippage-mediated deletions, there were > or = 5-bp identical runs at the recombination breakpoints. We propose that the dramatic increase in recombination results from enhancement of the effects of altered replication by the LIR, leading to recombinationally active initiating structures. Such interactions predict replication-related, MMR-independent genome changes.